Economic evaluation of the Diamer-Basha dam: Analysis with an integrated economic/water simulation model of Pakistan - Robinson, Sherman; Gueneau, Arthur (International Food Policy Research Institute, 2014)
This paper describes the potential impact on the economy of Pakistan of building the Diamer-Basha dam. An integrated system of economic and water simulation models is applied to Pakistan to analyze the economywide impacts of changes in water resources in the Indus river basin, focusing on agricultural and hydropower benefits provided by the Diamer-Basha dam under different climate scenarios. The model framework links separate economic and water models, drawing on the strengths of both approaches without having to compromise by specifying either a simplified treatment of water in an economic model or simplified economics in a water model. The model system is used to simulate the impact of economic growth and changes in water resources over the long run, focusing on agriculture and hydropower. The results of scenario analysis indicate that the Diamer-Basha dam would improve the resilience of Pakistan to adapt to climate shocks, providing increased hydropower capacity and enhanced ability to manage the water system to offset climate-induced variation in river flows.